URGENSI KOLABORASI RISET DALAM RANGKA ALIH TEKNOLOGI PENANGGULANGAN COVID-19 - Angga Wijaya Holman Fasa; Mahardhika Berliandaldo (Universitas Halu Oleo, 2021)
The coronavirus respiratory syndrome (COVID-19) pandemic has become a global public health problem. One of the main efforts to overcome this problem is research and development of technology in the health sector. This condition requires the readiness of the State Civil Apparatus (ASN), especially researchers and engineers, to increase the capacity or competence through technology transfer mechanisms in research collaboration schemes, both at the national and international levels. This study aims to find out, understand and explain two things, the urgency of research collaboration in the context of transferring COVID-19 countermeasures technology and strategic efforts to build research collaboration. This study uses a qualitative method with a descriptive analytical approach. The results of the study shows two things, first, that research collaboration in the context of technology transfer is significantly urgent to be implemented in order to encourage researchers and engineers to gain new knowledge about technology in the health sector, and second, strategic efforts that can be implemented by collaborating with researchers and engineers of credible research institutions in the health sector, and have implemented an open science policy which will significantly assist the technology transfer process without being constrained by intellectual property issues.